A Nationwide, Systematic, and Comprehensive Assessment of Surgical Capacity in Lebanon: Results of the Surgical Capacity in Areas With Refugees (SCAR) Study. Issue 6 (June 2019) - Kaafarani, Haytham M. A.; Khalifeh, Jawad M.; Ramly, Elie P.; Simon, David; Safa, Rawan; Khalil, Lana; Raad, Randa; Hoballah, Jamal J.
Abstract : Objective: We sought to perform a systematic, comprehensive, and nationwide cross-sectional analysis of surgical capacity in Lebanon. Background: Providing surgical care in refugee areas is increasingly recognized as a global health priority. The surgical capacity of Lebanon where at least 1 in 6 inhabitants is currently a refugee remains unknown. Methods: The Surgical Capacity in Areas with Refugees cross-sectional study included 3 steps: (1) geographically mapping all hospitals providing surgical care in Lebanon, (2) systematically assessing each hospital's surgical capacity, and (3) identifying surgical care gaps/disparities. First, a list of hospitals in Lebanon and their locations was generated combining data from the Lebanese Ministry of Health and Syndicate of Hospitals. Specialty, rehabilitation, and maternity facilities were excluded. Second, the validated 5 domain Personnel, Infrastructure, Procedures, Equipment, and Supplies (PIPES) tool was administered in each hospital through a face-to-face or phone interview. Hospitals' PIPES indices were computed; data were aggregated and analyzed for geographic and private/public disparities. Results: A total of 129 hospitals were geographically mapped; 20% were public. The PIPES tool was administered in all hospitals (100%). The mean PIPES index was 10.98 (Personnel = 14.91, Infrastructure = 15.36, Procedures = 37.47, Equipment = 21.63, Supplies = 24.78). The number of hospital beds, operating rooms, surgeons, and anesthesiologists per 100, 000 people were 217, 8, 16, and 9, respectively. Deficiencies in infrastructure were significant, whereby 62%, 36%, 16%, and 5% of hospitals lack incinerators, pretested blood, intensive care units, and computed tomography, respectively. Continuous external electricity was lacking in 16 hospitals (12%). Compared to private hospitals, public hospitals had a lower PIPES index (10.48 vs 11.1, P = 0.022), including lower Personnel and Infrastructure scores (12.31 vs 15.57, P = 0.03; 14.04 vs 15.7, P = 0.003, respectively). Geographically, the administrative governorates with highest refugee concentrations had the lowest PIPES indices. Conclusions: Evaluating surgical capacity in Lebanon reveals significant deficiencies, most pronounced in public hospitals in which refugee care is provided and in areas with the highest refugee concentration. Abstract : Supplemental Digital Content is available in the text